#### Answer

D. -3

#### Work Step by Step

We know that $\sqrt[3] -27=-3$, because $(-3)^{3}=-3\times-3\times-3=-27$.

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

D. -3

We know that $\sqrt[3] -27=-3$, because $(-3)^{3}=-3\times-3\times-3=-27$.

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.